2016
DOI: 10.30684/etj.34.7a.11
|View full text |Cite
|
Sign up to set email alerts
|

Optimization the Resistance Spot Welding Parameters of Austenitic Stainless Steel and Aluminum Alloy Using Design of Experiment Method

Abstract: This research aims to study the effect of RSW parameters on the sheer force of the spot welded for two materials {AISI 304L and AA 6061-T6} with (0.5 and 0.7 mm) thickness. Three values for each welding parameters (welding current, electrode force, squeeze time and welding time) are to be used. The effect of those parameters has been analyzed by using design of experiments (DOE) in order to determine and reduce the number of the tested specimens. The experimental tests have been done that are; shear, micro har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
1
5
0
Order By: Relevance
“…With increasing welding time, higher tensile strength is obtained, this is because the heat input that occurs is also greater, resulting in a strong tensile strength. But the connection is not always better, in the dissimilar metal point weld connection there is a condition where at 8 seconds the tensile strength decreases, this happens because the heat input exceeds the melting point of the material used so as to produce a wide weld metal area and deep penetration area, then the welding result will be damaged [19][20][21].…”
Section: Figure 6 Maximum Stress Vs Welding Timementioning
confidence: 99%
“…With increasing welding time, higher tensile strength is obtained, this is because the heat input that occurs is also greater, resulting in a strong tensile strength. But the connection is not always better, in the dissimilar metal point weld connection there is a condition where at 8 seconds the tensile strength decreases, this happens because the heat input exceeds the melting point of the material used so as to produce a wide weld metal area and deep penetration area, then the welding result will be damaged [19][20][21].…”
Section: Figure 6 Maximum Stress Vs Welding Timementioning
confidence: 99%
“…The RSW specimens were gripped with alignment tabs of a thickness equal to that of the specimens to ensure that the tensile force was applied to the weld spot and to avoid bending [47]. The average values have been taken from different measurements.…”
Section: Tensile Shear Testmentioning
confidence: 99%
“…The findings demonstrated that increasing the sheet thickness and welding current sheet thickness raised the strength of the welded components. Strength of welded parts decreased as electrode force and welding time were increased [21]. In contrast to past studies, which focused on a single area, the current work proposes a double RSW optimization strategy for high strength steel low alloys (DOCOL 500 LA).…”
Section: Introductionmentioning
confidence: 99%